WAYS OF SOLVING THE PROBLEM OF CHOLEDOCHOLITHIASIS IN PATIENTS WITH PATHOLOGY OF PARAPAPILLARY ZONE AND COMMON BILE DUCT - Ivashchenko, D.M.; Shevchuk, M.P.; Dudchenko, M.O.; Kravtsiv, M.I.; Prikhidko, R.A.; Zezekalo, E.O.; Zaiets, S.M. (World of Medicine and Biology, 2023)
The paper presents an analysis of the results of endoscopic treatment of choledocholithiasis in clinically severe cases. A retrospective and prospective analysis of the treatment of 161 patients with choledocholithiasis was conducted. Endoscopic papillosphincterotomy, mechanical lithotripsy, nasobiliary drainage and transpapillary stenting were performed to restore the bile passage and rehabilitate the extrahepatic bile ducts. Then we carry out a comparison of the efficiency of endoscopic lithoextraction in two groups of patients. The 1-st group – patients with large calculi of the common bile duct and normal anatomy of the parapapillary zone and choledochus, the 2-nd group – patients with choledocholithiasis and complicated anatomy – diverticuls of the parapapillary zone, stenosis or strictures of the extrahepatic bile ducts. Endoscopic papillosphincterotomy was performed in 151 patients. In 44 patients with diverticula of the large duodenal papilla, stones were removed by standard lithoextractors, in other 107 cases – mechanical lithotriptor was used. Stones were successfully removed in 98 patients. Lithotripsy was unsuccessful in 7 patients of 1-st group and in 2 patients of 2-nd group, and the reliability of lithotripsy did not differ in both groups. Endoscopic manipulations were equally effective in both groups.